Rectificación taxonómica y nomenclatural del presente status del taxón Liolaemus melanops Burmeister 1888 - Cei, José M. (2003)
The real status of the localised Liolaemus melanops Burmeister 1888 from Quelé Curá, Chubut, on the basis of its rediscovered original type, previously given as lost, is established. A reconsideration of the population units included in a general taxon “melanops”, is carried out. The formerly synonymized Liolaemus goetschi Müller & Hellmich 1938 from Río Negro sandy habitats is revalidated as separated species from L. melanops.